Concept of Corporate Social Responsibility and a Perspective on the Issue in Develoiing Country Context - Gurol, Yonca; Buyukbalci, Pinar; Bal, Yasemin; Ertemsir Berkin, Esin (ISTANBUL UNIV, 2010)
While determining their area of responsibilities, companies, attempt to develop their operations by taking opinions and expectations of all stakeholder groups in their complicated business networks into consideration. One of the questions here to answer is whether the companies exist to meet the expectations and needs of the community and the individuals or the community and the individuals exist for meeting the needs of the company. Corporate Social Responsibility (CSR) implementations, which develop within this framework, are especially worth to pay attention in the context of developing countries as these countries inherit a high potential in terms of market dynamics while, at the same time, do have a highly volatile market structure. Basing on this notion, this study first argues the conceptual framework and importance of CSR as a concept; then attempts to explain some important theoretical foundations coming from Institutional Theory, Stakeholder Approach and Strategic Perspective; and finally presents a brief look on certain implications of the issue in developing country context.
Keywords: Corporate Social Responsibility; Developing Counties; Stakeholder Approach; Institutional Theory; BUSINESS; MODEL; Government & Law